A novel experimental method to characterise the shear strength of concrete based on pre‐stressed samples. (30th January 2022) - Forquin, Pascal; Abdul‐Rahman, Reem; Saletti, Dominique
Abstract: The present paper describes a novel experimental method for characterising the confined shear strength of concrete or rock‐like materials based on the use of pre‐stressed sample. This method, called PS‐PTS (Pre‐Stressed Punch‐Through‐Shear), employs a metallic confinement cell that is first quasi‐statically deformed so the concrete sample can be introduced in between the cell jaws. The confinement force is transmitted to the sample in the unloading stage. It is shown that this initial pre‐load level can be predicted by an elastic closed‐form solution. Strain‐gauges glued on the cell allow the confinement level applied to the sample to be experimentally measured during the pre‐stressing stage and the shear stage. In the next stage, the central part of the sample is subjected to a differential displacement towards the lateral parts by means of a hydraulic press so the confined shear strength of the tested material can be deduced. The results are compared to the data previously obtained with an "oedometric" confinement cell in terms of confinement stresses and shear strength. Highlights: A Pre‐Stressed Punch‐Through‐Shear technique is proposed based on pre‐loaded cell. A close‐form solution predicts the level of pre‐load applied to the sample. The cell is instrumented with strain gauges, so the applied forces are measured. The technique is applied to characterise the confined shear strength of concrete. Results are compared to those obtained with the 'Oedo‐PTS' testing method.